PERENCANAAN DAN PENGENDALIAN PERSEDIAAN BAHAN BAKU OPAK DENGAN PENDEKATAN MRP (MATERIAL REQUIREMENT PLANNING) - Koto, Zul Hamly Yahya; Zaharuddin, Zaharuddin; Harahap, Uun Novalia (JURNAL REKAYASA SISTEM INDUSTRI, 2024)
UMKM Eka Jaya Opak is a business unit in the food industry that utilizes cassava as its main raw material. Its products have been marketed in several cities in Sumatra and Java. However, the company faces challenges in ordering raw materials and inadequate inventory, forcing them to purchase similar products from nearby businesses. This study aims to plan and control raw material inventory and determine the appropriate ordering period. The Exponential Smoothing method is used for forecasting and yields results with MAD = 3073.1, MSE = 13448930, and MAPE = 8.90%. The forecasting results are then analyzed using Material Requirement Planning (MRP) methods with LFL, EOQ, and POQ techniques to find optimal orders with minimum costs. The POQ technique is selected with a total cost of Rp. 2,543,898,000, which is better than Lot For Lot (Rp. 2,548,488,000) and Economic Order Quantity (Rp. 3,059,174,393). Therefore, the MRP method with the POQ technique is chosen for planning and controlling raw material inventory at UMKM Eka Jaya Opak